Sports education and sports training/La enseñanza deportiva y el entrenamiento deportivo - Heriberto Rodríguez Verdura; Luís Leonardo León Vázquez; Joel Ernesto de la Paz-Ávila (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
The article arises from the need to contextualize sports teaching and to establish the characteristics that differentiate it from sports training from the definition of its components and the system of pedagogical categories, principles and regularities that are inherent to it. All this, in order to give an answer to the latent contradiction today in the initial and continuous training of the sports teacher, as well as to the way of acting and performing their professional functions in correspondence with the real demands of the context of the sphere of action (basic link) where their professional practice is indicated. The objective of the research is to reflect on the components, categories and system of principles that characterize sports teaching, differentiating them from those of sports training. An extensive bibliographic review was carried out in national repositories and in the EBSCO HOST, Dialnet, SPORTDiscus and Google Scholar databases, which collect articles and journals of national and international scope. The analyses carried out offer a concrete and applicable answer for the improvement of the career curriculum, as well as of the normative documents for the performance of sports teachers in the basic link.